"Foundation Program Vol.2: Relational Database Management System Client Server Concepts, Introduction to Web Technologies Version 1.0" - Hanumesh (V J); Acharya (Seema) ("Plot No: 44, 3rd Cross, Electronics City, Hosur Road,Bangalore - 560 100", 2006)
Relational Database Management System ; Client Server ; Web Technologies
Keywords: Relational Database Management System ; Client Server ; Web Technologies